Associação do polimorfismo rs266729 do gene da adiponectina com consumo alimentar, parâmetros antropométricos, bioquímicos, inflamatórios e do estresse oxidativo em pacientes com retinopatia diabética - Brito, Vanessa Polyana de Sousa (2020)
Diabetic retinopathy is a progressive condition with microvascular changes that lead to retinal ischemia, retinal permeability, retinal neovascularization and macular edema. If left untreated, patients with RD can suffer severe visual loss. The rs266729 (11377CG) polymorphism, located in the adiponectin promoting region, has been related to a higher risk of diabetes and possible association with RD associated with insulin therapy. In this sense, the present study aimed to analyze the influence of the rs266729 polymorphism of the adiponectin gene on food consumption, anthropometric, biochemical, inflammatory parameters and oxidative stress in addition to the RD stages. This is a cross-sectional epidemiological study, conducted by 98 individuals seen at the Vision Unit of the University Hospital Lauro Wanderley of the Federal University of Paraíba (HULW / UFPB). Patients diagnosed with DR with type 2 diabetes mellitus (DM2) of both sexes were included, divided into two groups according to the rs266729 genotypes. The genotypes were determined by the PCR-RFLP technique in DNA isolated from leukocytes. Blood samples were used for biochemical tests (glucose, HbA1C, total cholesterol and fractions, creatinine, C-reactive protein), malondialdehyde (MDA) and total antioxidant capacity (CAT). In addition, blood pressure, anthropometric data and food consumption (24-hour recalls) were evaluated. Limb amputation and insulin therapy were more frequent in individuals with the G allele (CG + GG group) when compared to CC individuals. However, the consumption of saturated fat was higher in the GC + GG group than in the CC group. Logistic regression analyzes showed the presence of G allele was associated with limb amputation (p <0.05). The occurrence of the adiponectin rs266729 gene polymorphism, although it contributed to the increase in the consumption of saturated fatty acids, has no impact on the cardiometabolic, inflammatory and oxidative stress variables in individuals with RD. Thus, rs266729 may not be a genetic marker that determines worsening of cardiometabolic, inflammatory and oxidative stress markers, however it is associated with limb amputation in patients with RD.